Pengaruh Literasi Keuangan, Financial Technology, dan Motivasi Utilitarian Terhadap Pengelolaan Keuangan Mahasiswa - Eka Fitri Nurjannah; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effects of financial literacy, financial technology, and utilitarian motivation on student financial management using explanatory quantitative methods. Research subjects were Accounting students at UPN